Panglima Polem Basketball Club Banda Aceh 2023/2024 Management - Ifwandi, Ifwandi; Mansur, Mansur; Fajrial, Jul; Karimuddin, Karimuddin; Masri, Masri; Masitah, Nurul (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. High-achieving athletes will be developed and club activities will be sustained with effective administration. The management of the Panglima Polem Basketball Club Banda Aceh in 2023–2024 will be examined and evaluated as part of this study. Materials and Methods. The research methodology used in this study is qualitative. Qualitative descriptive research is used in this kind of study. Using the snowball sample subject determination technique, the study's data sources or subjects are four athletes, two coaches, and two administrators. Data gathering methods used in this study included observation, interviews, and documentation. The data results were then analysed through data collection, data reduction, data presentation, and conclusion drafting. Results. The study's findings clarify that the Panglima Polem club's management involves the following procedure: 1) Planning has gone smoothly, with a well-defined training programme and reliable funding sources being essential to managing a sports organisation that aims to meet the objectives established by the Panglima Polem club. 2) With a club organisational system that is operated in accordance with each member's responsibilities and functions, organising has been moving smoothly. Administrators, coaches, and athletes work well together to build accomplishments for the Panglima Polem club. 3) Although there are training and coaching programmes in place and athletes receive development every three months, the implementation process has not been ideal, frequently encountering difficulties when utilising the infrastructure and facilities needed for training. Nevertheless, implementation has been going fairly well. 4) Supervision has been going pretty well with the actions that have been taken in the stages of monitoring and evaluation to improve the improvement of a sports organisation, particularly in the area of basketball to achieve good basketball achievements so that members can become athletes with a national and international level of accomplishment. Conclusion. The key to accomplishing the club's objectives is having a well-defined training programme and reliable financial sources. The club's accomplishments have been facilitated by the organisational framework that is put in place in accordance with each task and role, as well as the positive collaboration between coaches, athletes, and administrators. Club performance evaluation, coach development tactics, resource management, player wellness initiatives, enhancing training quality through technology, and the impact of social support are some of the main recommendations. Reviewing the club's branding and marketing plans is also crucial, as is the players' mental and emotional growth. It is anticipated that this strategy would enhance the club's overall performance and achievement.